Crystallinity and formation of silica in Palaeozoic shales: A new quantification calculation method based on X-Ray diffraction. (April 2023) - Liu, Guoheng; Liu, Keyu; Zhai, Gangyi; Zhao, Jianhua; Guo, Zongguang
Abstract: Based on X-ray diffraction (XRD) data, we suggest a new parameter for describing quartz crystallinity. The parameter is determined by analysing the quartz's fifth peak's perfection degree at (68°–68.6°)/2θ in XRD data. In contrast to other computation techniques, the new one does not require the subtraction of the environment background value from the XRD patterns, preventing the huge deviation appearance introduced artificially. Furthermore, the values obtained by the new method exhibit a decreased standard deviation compared with those obtained by previous methods following data normalisation to remove the influence of magnitude order, demonstrating better precision and stability. It has been discovered that the origin of silica, which was once thought to be a significant factor affecting silica crystallinity, has no effect. The abundance of silica and a lack of growth space can all inhibit quartz crystal growth. The appearance of endogenous pyrobitumen and exogenous hydrocarbon can possibly prevent quartz crystal growth. Highlights: A new effective parameter for determining quartz crystallinity is proposed. The origin of silica has been found to have no effect on silica crystallinity Lower temperature, high silica abundance, lack of growth space, and hydrocarbon inhibit micro-quartz crystal formation